Ground Water Level Variability and their Cost Implications: A Case of Keiyo North Sub-County, Elgeyo Marakwet County, Kenya - Kiptum, A.; Chebet, C. (Africa Environmental Review Journal, 2017)
Ground and surface water are the main sources of water in Kenya and world over. Due to climate change, environmental degradation as well as population pressure, water has become quite scarce and thus the need to exploit more ground water so as to satisfy the ever increasing demand. However, there has been a decline in the ground water level which has been linked to the disruption of the hydrologic cycle by human activities. As the water table drops, the depths of wells increase and so does the cost of drilling them. Similarly, a decline in water table often leads to a reduction in the amount of water in wells and thus unmet water demands in households. The households are then forced to extend their wells and thus incur some costs. This study therefore sought to determine the water table variability over time and their cost implications. The study was done in Keiyo North sub-County, Elgeyo Marakwet County, Kenya. Field surveys, structured questionnaires and interviews were the primary data sources while review of relevant published literature formed secondary sources. A total of 318 respondents were interviewed. The results revealed that 88% of households used wells as the main source of water while 12% rely on other sources of water such as rivers, streams, springs and piped water. Average water consumption per household was, 159.64 litres per day, while, 112 household were found to have extended their wells at an average cost of Ksh. 159.9 per foot. The total depth extended by the sampled households was 390.6 feet and the estimated total cost was Ksh. 62,284.142 with an average of Ksh. 556 per household. In conclusion, there has been a decline in ground water level which has led to reduced ground water supply in household wells. This has resulted in households extending their wells and hence incurring costs. The resultant cost of accessing ground water informs the water resource managers and policy makers on the need to address the ground water recession.